Q: 5x plus 3 equals 3 plus 5x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

-4x + 3 = -5x + 3add 5x to each sidex + 3 = 3subtract three from each sidex = 0

3 + 5x = 38 -> 5x = 35 -> x = 7

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

Multiply the bottom equation by -1

Related questions

33

5x+3 = -17 5x = -17-3 5x = -20 x = -4

5x + 3 = -12 5x =-12-3 =-15 x = -3

5x - 4x = 13 - 3 ie x = 10

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

-4x + 3 = -5x + 3add 5x to each sidex + 3 = 3subtract three from each sidex = 0

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

3 + 5x = 38 -> 5x = 35 -> x = 7

Multiply the bottom equation by -1

Yes.

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3

-6x+3 = -7-5x 7+3 = 6x-5x 10=x